AN EXPERIMENTAL STUDY OF ORGANIC POLLUTANT EFFECTS ON TIME DOMAIN INDUCED POLARIZATION MEASUREMENTS - Martinho E.; Almeida F.; Senos Matias M.J. (My University, 2006)
Laboratory results from the application of the time domain induced polarization method to the study of organic contamination in soil samples are presented. IP effects for uncontaminated and contaminated (gasoline, isopentane, toluene and benzene) clayey soil samples were measured in the laboratory. The data were processed to obtain the sample resistivity, resistance, chargeability, capacity, amplitude and decay constant, in order to establish their interdependency, as well as, the behaviour of the main experimental variable involved, that is, the degree of contamination. The results show that minimum values for the chargeability, decay constant and capacity, are reached for a certain amount of pollutant, and a contamination model is proposed using the equivalent circuit theory applied to IP phenomenon. Thus, a process whereby organic molecules coat clay particle surfaces is proposed and a decrease in the expected membrane polarization effect can explain the interaction between clay minerals and organic molecules. Finally, the capacity allows a better separation between contaminated and uncontaminated areas than that provided by chargeability and decay constant, as it defines a threshold, which does not depend on the pollutant concentration. © 2005 Elsevier B.V. All rights reserved.
Keywords: CONTAMINATION; HYDROCARBONS; INDUCED POLARIZATION; RESISTIVITY